Sikap Tokoh dalam Novel Burung-Burung Cahaya Karya Jusuf AN: Sebuah Analisis Psikologi Sastra - Awalludin, Awalludin; Nilawijaya, Rita (UNIB Press, 2021)
The purpose of this study was to describe the attitudes of the characters in Jusuf AN novel Burung-Burung Cahaya through psychological analysis of literature. The method used in this research is descriptive method with literary psychology approach. The technique used to collect data is the literature study technique. After that, the data were analyzed using creation analysis techniques. Based on the results of the analysis and discussion, it shows that in the novel Burung-Burung Cahaya by Jusuf AN, there are several elements of attitude which include three components, namely cognitive, affective, and conative which are actualized with an attitude of compassion, obedience to the rules, attentiveness, and independence. The affective component is an emotional component related to a person's emotional life, such as pleasure, hate, bored, fear, or other feelings about something. The conative component is a behavior component which is a tendency to behave or act on certain objects. These three attitudes are shown by several characters including the characters Aku, Zulaikha, Shinta, and Sulam, because only these four characters can be identified in Jusuf AN's novel Burung-Burung Cahaya, while the other characters cannot be shown thoroughly because at a glance as a complement to the storyline. This made it difficult for researchers to determine the nature and attitudes in the characterization of Jusuf AN novel Burung-Burung Cahaya. Thus, the novel Burung-Burung Cahaya by Jusuf AN is a worthy and good novel to be read by all circles, because the novel contains many positive values and use values in social life.